A Fast and Reliable Hybrid Data Delivery Protocol for Large-Scale Heterogeneous Sensor Networks. (22nd January 2012) - Kang Kang, Sanggil Sanggil; Lim Lim, Yujin Yujin; Lopez Lopez, Wilmarc Wilmarc; Hwang Hwang, Hoyoung Hoyoung
Abstract : We propose a hybrid data delivery method for the large-scale heterogeneous sensor networks, which is a fast and reliable delivery protocol for the aggregated data from the sinks to the GW. We develop a new multicriteria-ranking algorithm which determines multiple forwarders for each hop by ranking neighbor nodes. To rank the nodes, we compute the fitness value using features for each node such as the received signal strength, nodal delay, and hop distance. We determine the time of sending among forwarders using the waiting time assignment algorithm. In the experimental section, we show that our method outperforms conventional data delivery protocols in terms of data delivery ratio and end-to-end delay.